MEANING AS A MARKER OF METAPHORICITY TOWARDS A COMPUTATIONAL IDENTIFICATION OF METAPHOR IN THE EVER-GLORIOUS QUR’ĀN - Amal Abdelsattar Metwally; Dalal Mahmoud Elgemei (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2022)
This work represents a novel direction for computational linguistics research on metaphor in the Ever-Glorious Qur’ān. The present study proposed a basic/non-basic meaning criterion as a marker for the computational identification of metaphor in the Ever-Glorious Qur’ān. The corpus was Sūrat Hūd, where manual identification for candidate metaphors was conducted by referring to four authentic exegeses, namely Tafsīr Aṭ-Ṭabarī (2010), Az-Zamakhshari (2007), Al-Qurṭubi (1964) and Ash-Sha’rāwi (1997) as well as Yūsuf ‘Ali interpretation of the meanings of the Ever-Glorious Qur’ān (1992). 22 metaphors were identified and classified based on the proposed semantic criterion. The data were analyzed both qualitatively and quantitatively, and candidates were classified into three categories depending on their meaning and their degree of metaphoricity. The study drew on the conceptual theory of metaphor by Lackoff Johnson (1980), studies on metaphors in the Ever-Glorious Qur’ān, as well as computational studies of metaphor, in general, to finally arrive at a criterion that describes the meaning of metaphor towards a computational identification of metaphors in the Ever-Glorious Qur’ān. The study proposed a software input to detect metaphors by identifying their semantic features.